Appraisal of the Effect of TQM and Entrepreneurship on Organizational Performance of Rangsazi Company of Iran - Mehdi Ajalli; Mohammad Mahdi Mozaffari; Mina Akbari Ghalee Jough (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aimed to investigate the effect of total quality management and entrepreneurship on the organizational performance of Iran Paint Company using a descriptive correlation method.Methodology: The study's statistical population was 200 employees of Iran Paint Company, 132 selected by simple random sampling. For data collection, three questionnaires, Moghimi Inclusive Quality Management (2009), Antoncic and Hisrich Entrepreneurship (2003), and Carabulot Organizational Performance Questionnaire (2015), were used. Their reliability through Cronbach's alpha coefficient was 0.86 and 0.82, respectively. And 0.89 was obtained. A structural equation model test was used to analyze the data using SPLS software.Findings: The results showed that total quality management and entrepreneurship have a positive and significant effect on the organizational performance of Iran Paint Company. The results also showed that entrepreneurship positively and significantly affects organizational performance. Finally, the results show the impact of total quality management on organizational performance with the role of entrepreneurial mediator.Originality/Value:  In total quality management and entrepreneurship, organizations that care about these variables perform better in achieving high levels of growth and development.